Analysis of the Determining Factors of MSME Taxpayer Compliance Reviewed from the Level of Tax Understanding and Tax Policies - Ipanka, Desi Putri; Mutia, Lesti Silva; Apriliyanti, Nikita Dwi; Shofiah Nailin Najah; Anne Tonthawi (Universitas Gorontalo, 2026)
This study aims to analyze the factors influencing taxpayer compliance among micro, small, and medium enterprises in terms of tax understanding and tax policy. This study employed a qualitative descriptive approach to obtain an in-depth understanding of taxpayer compliance behavior among business owners. Data collection techniques were conducted through interviews, observation, and documentation involving selected informants who actively managed their businesses and fulfilled tax administrative requirements. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that taxpayer compliance is influenced by limited tax understanding, low digital literacy, limited tax socialization, and the complexity of digital-based tax administration systems. In addition, most business owners still implement simple financial recording practices, resulting in less optimal tax administration. The study concludes that simplifying tax administration, strengthening tax education, and providing direct assistance are important efforts to improve voluntary taxpayer compliance among micro, small, and medium enterprises.